Comparative politics of Southeast Asia an introduction to governments and political regimes - Croissant, Aurel (Springer texts in political science and international relations, 2022)
"This textbook provides a comprehensive introduction to the political systems of all ASEAN countries and Timor-Leste from a comparative perspective. It investigates the political institutions, actors, and processes in eleven states, covering democracies as well as autocratic regimes. Each country study includes an analysis of the current system of governance, the party and electoral system, and an assessment of the state, its legal system, and administrative bodies. Students of political science and area studies also learn about processes of democratic transition and autocratic resilience, as well as how civil society and the media influence the political culture in each country. This second edition features revised and updated versions of all country studies and a new chapter that discusses the trends of democratization and autocratization in Southeast Asia in the late 20th and early 21st centuries." --Publisher's description.